Characteristics of Extraneural Tuberculosis in Patients with Tuberculous Meningitis Hospitalized at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia in 2017–2021 - Grazielle, Grazielle; Ganiem, Ahmad Rizal; Sobaryati, Sobaryati; Dian, Sofiati; Santoso, Prayudi (Althea Medical Journal, 2024)
Background: Tuberculous (TB) meningitis is the most severe manifestation of extrapulmonary TB and contributes to a high mortality rate. The presence of extraneural TB may raise suspicion of TB meningitis (TBM). This study aimed to explore the characteristics of extraneural TB in TBM patients.Methods: This was a cross-sectional descriptive study using secondary data from medical records of TBM patients admitted at Dr. Hasan Sadikin General Hospital Bandung, Indonesia from 2017 to 2021. Demographic and clinical data were collected, including HIV status. TBM cases were classified into grades I, II, and III using Medical Research Counsil (MRC) criteria that were based on Glasgow Coma Scale (GCS) score and the presence of focal neurological deficits. The clinical classification diagnosis of TBM was made based on the Marais diagnostic criteria which included several diagnostic items and corresponding scoring which further divides TBM into three classes. Extraneural TB is defined as the finding of TB outside the nervous system. Disseminated TB was diagnosed based on the finding of ≥2 infected locations.Results: During the study period, 497 medical records were analyzed. Most TBM patients experienced Grade II (76.9%) and extraneural TB site was found in 65.4%, with pulmonary TB as the common site (77%). The highest mortality rate was in disseminated TB (50%). The finding of extraneural TB did not differ between HIV-negative and HIV-positive patients (67.8% vs. 67.9%; p=0.101).Conclusion:  The presence of extraneural TB is common in patients with TBM. Therefore, extraneural TB evaluation is important to ensure TBM diagnosis. Further studies are needed to explore factors related to TBM diagnosis to ensure TBM patient’s wellbeing.